2019
DOI: 10.3386/w26113
|View full text |Cite
|
Sign up to set email alerts
|

Skin or Skim? Inside Investment and Hedge Fund Performance

Abstract: Business and ColumbiaUniversity. We thank Billy Xu for excellent research assistance. See https://www.skinorskim.org for Form ADV data used in this paper. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
4
9
0
Order By: Relevance
“…For instance, many prior studies suggest that the size of insider shareholding affects the financial performance (Jensen and Meckling (1976): Fama & Jensen, 1983; Gupta & Sachdeva, 2017). However, the outcome indicates that insider shareholding has no influence on financial performance, itself consistent with findings of Agrawal and Knoeber (1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, many prior studies suggest that the size of insider shareholding affects the financial performance (Jensen and Meckling (1976): Fama & Jensen, 1983; Gupta & Sachdeva, 2017). However, the outcome indicates that insider shareholding has no influence on financial performance, itself consistent with findings of Agrawal and Knoeber (1996).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Fama and Jensen (1983) point that such an increase can result in managerial entrenchment. Recently, Gupta and Sachdeva (2017) tested a comprehensive data set of hedge funds on financial performance of firms with much or little insider shareholding,—using multiple linear regression models. It is found that firms with insider investment perform better than others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this spirit, we expect hedge funds to leave more money on the table when agency frictions are more severe (e.g., when their leverage is high, their reputation is low, and or when their assets are less liquid). A complementary point of view is proposed by Gupta and Sachdeva (2018). They argue that there is an important difference between inside and outside equity capital.…”
Section: Hypothesesmentioning
confidence: 99%
“…Consistent with this argument, we find that funds engage in fewer premature position closures if they have a longer track record, a more successful track record, or more liquid assets. We then test a recent idea by Gupta and Sachdeva (2018): hedge funds with high inside ownership (by their managers) may not want to dilute the returns on this inside capital and may thus be reluctant to raise additional equity capital from investors. We indeed find that hedge funds with high inside capital leave more money on the table, in line with these funds choosing to operate on a smaller scale.…”
mentioning
confidence: 99%
“…This figure able to generate the investors' confidence and interest to invest further in this firm. On the other hand, other factors that investors look at when making the investment decisions are the insider shareholder (Akshita & Sharma, 2015;Gupta & Sachdeva, 2019), audit committees (Crisan & Fulop, 2014), strong board independence (Christensen, et al, 2010), the board size, CEO duality and the corporate structure of the firm (Mallin, 2016;Jakpar et al, 2019).…”
Section: Impact Of Corporate Governance and Human Governance On Firm mentioning
confidence: 99%